The treatment of lung cancer: scientific facts facing with therapeutic choices. - Toraldo, Domenico Maurizio (Medicina e Morale, 2001)
The lung cancer constitutes one of the main causes of death in Europe. This pathology; if inoperable, has a poor prognosis and 80 per cent of the patients dies within one year from the prognosis. So; an effective treatment constitutes a public health priority and a topic of continuous scientific debate. The early diagnosis afford the possibility to the patient to take advantage of the surgical treatment that can solve the pathology. The polichemtherapy and the radiotherapy often fail and, in the best cases, could lenghten the patient's life of some month, at the cost of important sufferings. In the clinical routine, in many italian hospitals, even if a standard diagnostic- therapeutic protocol does not exist, the medical treatment is frequently proposed without an adequate informed consent that explain to the patient the complexity of the treatment and an active participation of the sick person to the decision that concern him/her. The Author, through a review of the recent literature, underlines the matter from the technical point of view and, contemporaneously, the numerous bioethical adn deontological issues risen from the absence both of an ethics of the diagnosis/therapy-related communication and an effective care relationship between the physician and the patient. The decisive role of the medical doctor is analysed in the last phases of the patient's and the efficacy of the palliative medicine to relieve the patient of the pain and to control the symptoms, like a form of respect of the dignity of the human person. Finally, the Author hope the need for an ethical and deontological education of the hospital physicians to acquire a more deep awareness of the moral values at the stake in the clinicla practice.